A phase I study of a novel potential intravaginal microbicide, PRO 2000, in healthy sexually inactive women. Issue 2 (1st April 2000) - Van Damme, Lut; Wright, Ann; Depraetere, Katrien; Rosenstein, Isobel; Vandersmissen, Veerle; Poulter, Len; McKinlay, Margo; Van Dyck, Eddy; Weber, Jonathan; Profy, Al; Laga, Marie; Kitchen, Val
Abstract : Background: Although the male condom provides a reliable means of preventing HIV transmission, a broader choice of methods is required particularly in circumstances where the negotiation of condom use is difficult. Development of new products that may be effective as topical vaginal microbicides is the focus of a great deal of research activity currently. The novel agent PRO 2000, a naphthalene sulphonate derivative with in vitro activity against HIV and other sexually transmissible pathogens, is one such compound. We have studied the local and systemic safety and tolerance of a vaginal gel formulation of this agent at two concentrations (0.5% and 4%) over a 2 week period of daily exposure in two cohorts of healthy sexually abstinent women (one in London, UK, and the other in Antwerp, Belgium). Methods: This was a randomised, placebo controlled, double blind, three arm clinical trial conducted on two sites. Macroscopic evidence of genital epithelial changes was sought using colposcopy and evidence of microscopic inflammation was acquired using high vaginal biopsy from predetermined sites (UK cohort only). Blood levels of PRO 2000 were measured and laboratory safety tests, including coagulation screens, were performed. The impact on vaginal ecology was also assessed. Results: 73 women were enrolled across both sites (36 UK, 37 Belgium); 24, 24, 25 in the 4%, 0.5%, and placebo groups respectively. Of these, 70 completed 2 weeks' exposure to the study gel. Three (all in the 4% group) withdrew owing to adverse events which were possibly or probably gel related. Cervicovaginal abrasion was seen colposcopically in three subjects after 14 days of gel use (two in the 4% group and one in the placebo group). Genital ulceration was not seen during gel use in any of the subjects who completed the study. Histological evaluation of vaginal biopsy samples (36 women only) showed evidence of increased inflammatory signs in one participant of the 4.0% group. One volunteer in the placebo group had moderate inflammation at screening and at follow up. Severe inflammation was not seen among any of the subjects tested. Plasma levels of PRO 2000 and laboratory safety tests showed no evidence of systemic absorption. No impact was seen on normal vaginal ecology in the UK cohort where samples were taken 12 hours after the last gel application. Conclusion: In this phase I study PRO 2000 gel was found to be generally well tolerated with promising local and systemic safety profiles. The 0.5% gel was better tolerated than the 4% gel as fewer genital epithelial adverse events were seen in the former. Phase II studies are about to begin in sexually active women.